Late-career language teachers in Austria and the UK: Pathways to retirement. (May 2022) - Babic, Sonja; Mairitsch, Astrid; Mercer, Sarah; Sulis, Giulia; Jin, Jun; King, Jim; Lanvers, Ursula; Shin, Sun
Abstract: This article seeks to explore personal and socio-contextual factors that supported or hindered the wellbeing of 13 late-career language teachers from Austria and the UK. Data were generated through in-depth life-history interviews, and analysed following a Grounded Theory approach (Charmaz, 2006). Findings revealed the interplay of various personal and socio-contextual factors that influenced teachers' wellbeing and willingness to stay in the profession. Findings also showed four different pathways to retirement: Perceived stress and wanting to leave the profession; loved being a teacher but mentally preparing for retirement; busy with work, not thinking about retirement; and, thriving and not planning retirement. Highlights: Thirteen late-career teachers from Austria and the UK participated in the study. Interplay between personal and contextual factors that influence late-career teacher, retention and wellbeing. Perceived saturation with the profession and changes in the respective countries' educational systems caused stress. Passion for teaching, sense of meaning, and positive workplace culture supported participants' long-lasting careers. Findings reveal four pathways to retirement in relation to participants' wellbeing and willingness to stay.